Water-Based Suspensions of Iron Oxide Nanoparticles with Electrostatic or Steric Stabilization by Chitosan: Fabrication, Characterization and Biocompatibility; Sensors; Vol. 17, iss. 11 - Kurlyandskaya G. V. Galina Vladimirovna; Litvinova L. S. Larisa; Safronov A. P. Alexander Petrovich; Shupletsova V. V. Valeria; Tyukova I. S. Irina; Khaziakhmatova O. G. Olga Gennadjevna; Slepchenko G. B. Galina Borisovna; Yurova K. A. Kristina; Cherempey E. G. Elena Gennadjevna; Kulesh N. A. Nikita Aleksandrovich; Andrade R. Ricardo; Beketov I. V. Igor; et al. (2017, 2017)
Title screen